2013
DOI: 10.1007/s00774-013-0481-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in statin users: a population-based analysis from a Spanish cohort

Abstract: We studied 2,315 subjects (1,422 women and 893 men) from the Camargo Cohort and analyzed the differences in BMD between statin or non-statin users. We also studied effects of the type of statin, dose, pharmacokinetic properties, and length of treatment on bone mineral density (BMD). Of the subjects, 478 (21 %) were taking statins (256 women and 222 men). Overall, they had higher BMD than non-users (p < 0.0001). In adjusted multivariate models, women taking statins had higher BMD at femoral neck (p = 0.002) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Statins are drugs with seemingly multiple actions, for which a possible effect on bone mass has been pointed out. However, such an effect is still discussed, and conflicting results have been published in this regard [51]. This is the first study about statin use and bone microarchitecture, and we found trabecular abnormalities at the distal tibia in men.…”
Section: Discussionmentioning
confidence: 76%
“…Statins are drugs with seemingly multiple actions, for which a possible effect on bone mass has been pointed out. However, such an effect is still discussed, and conflicting results have been published in this regard [51]. This is the first study about statin use and bone microarchitecture, and we found trabecular abnormalities at the distal tibia in men.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, lipids and lipoproteins, which are elevated in abdominal obesity, have been shown to inhibit osteoblast differentiation and to enhance osteoclast differentiation and survival (12, 24). Statin therapy to lower hyperlipidemia is associated with increased BMD and decreased fracture risk (25, 26) and bisphosphonates lower serum LDL cholesterol and apoB (27), supporting a connection between bone and lipid metabolism. In addition, vitamin D levels are reduced in patients with abdominal adiposity (28), in part due to sequestration of vitamin D, a fat soluble molecule, in adipose tissue.…”
Section: Discussionmentioning
confidence: 97%
“…The study was approved by the local Ethics Committee, and all subjects gave written informed consent. Details of the Camargo Cohort Study have been previously reported [12,13]. On February 2010, all men included in the Camargo cohort (n = 520) were included in our study.…”
Section: Methodsmentioning
confidence: 99%